Diagnostic Mutation Profiling and Validation of Non–Small-Cell Lung Cancer Small Biopsy Samples using a High Throughput Platform. Issue 5 (May 2015) - Quinn, Anne Marie; Hickson, Nicholas; Adaway, Megan; Priest, Lynsey; Jaeger, Erich; Udar, Nitin; Keeling, Catherine; Kamieniorz, Martyna; Dive, Caroline; Wallace, Andrew; Byers, Richard J.; Newman, William G.; et al.
Abstract : Background: A single platform designed for the synchronous screening of multiple mutations can potentially enable molecular profiling in samples of limited tumor tissue. This approach is ideal for the assessment of advanced non–small-cell lung cancer (NSCLC) diagnostic specimens, which often comprise small biopsies. Therefore, we aimed in this study to validate the mass spectrometry-based Sequenom LungCarta panel and MassARRAY platform using DNA extracted from a single 5 μM formalin-fixed paraffin-embedded tissue section. Methods: Mutations, including those with an equivocal spectrum, detected in 90 cases of NSCLC (72 lung biopsies, 13 metastatic tissue biopsies, three resections, and two cytology samples) were validated by a combination of standard sequencing techniques, immunohistochemical staining for p53 protein, and next-generation sequencing with the TruSight Tumor panel. Results: Fifty-five mutations were diagnosed in 47 cases (52%) in the following genes: TP53 (22), KRAS (15), EGFR (5), MET (3), PIK3CA (3), STK11 (2), NRF-2 (2), EPHA5 (1), EPHA3 (1), and MAP2K1 (1). Of the 90 samples, one failed testing due to poor quality DNA. An additional 7 TP53 mutations were detected by next-generation sequencing, which facilitated the interpretation of p53 immunohistochemistry but required 5 × 10 μM tumor sections per sample tested. Conclusions: The LungCarta panel is a sensitive method of screening for multiple alterations (214 mutations across 26 genes) and which optimizes the use of limited amounts of tumor DNA isolated from small specimens.